Hadis Tarbawi Sebagai Landasan Filosofis dan Praktis dalam Mewujudkan Pendidikan Islam di Sekolah - Fitriani Nurhayati (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
ABSTRACT Islamic education in the modern era faces a significant challenge in balancing academic achievement with spiritual and character development. This research aims to analyze the urgency of Hadis Tarbawi (educational traditions of the Prophet) as a fundamental basis for realizing the goals of Islamic education in schools. Using a qualitative method with a literature study approach, this article examines the classification of Hadis covering moral, intellectual, and spiritual aspects. The results indicate that Hadis Tarbawi is not merely a doctrinal text but a practical guide for forming individuals who are faithful, knowledgeable, and possess noble character. The success of Islamic education relies heavily on integrating Hadis values into the curriculum and creating a school environment based on the principles of Tarbiyah Nabawiyah (Prophetic education). This integration helps build a generation that maintains a balance between worldly knowledge and faith, while possessing strong moral integrity to face global challenges.